Reflections on five years of evaluating semantic search systems. (17th May 2010) - Uren, Victoria; Sabou, Marta; Motta, Enrico; Fernandez, Miriam; Lopez, Vanessa; Lei, Yuangui
Evaluations of semantic search systems are generally small scale and ad hoc due to the lack of appropriate resources such as test collections, agreed performance criteria and independent judgements of performance. By analysing our work in building and evaluating semantic tools over the last five years, we conclude that the growth of the semantic web led to an improvement in the available resources and the consequent robustness of performance assessments. We propose two directions for continuing evaluation work: the development of extensible evaluation benchmarks and the use of logging parameters for evaluating individual components of search systems.